2023
DOI: 10.1182/bloodadvances.2022007679
|View full text |Cite
|
Sign up to set email alerts
|

Absolute neutrophil count by Duffy status among healthy Black and African American adults

Abstract: Many people of African ancestry have lower absolute neutrophil counts (ANC) without increased risk for infection. This is associated with the Duffy null phenotype (non-expression of the Duffy antigen on red blood cells), which is commonly found in those of African descent. Currently, there are no studies that compare the ANC of individuals with Duffy null phenotype to those with Duffy non-null phenotypes within a self-identified Black population. This study aimed to assess the impact of Duffy status on ANC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
1
33
3
Order By: Relevance
“…The erythroid silent variant (FyES), though providing malarial protection, loses this developmental cue, resulting in a neutrophil phenotype with altered surface markers and increased propensity to leave circulation ( 64 , 65 ). The observed neutropenia, historically called “benign ethnic neutropenia” and now more accurately “Duffy-associated neutrophil count” (DANC), does not eliminate effective inflammatory immune responses and is hypothesized to be asymptomatic in otherwise-healthy patients ( 66 68 ).…”
Section: Ackr1 Structure and Functionmentioning
confidence: 99%
“…The erythroid silent variant (FyES), though providing malarial protection, loses this developmental cue, resulting in a neutrophil phenotype with altered surface markers and increased propensity to leave circulation ( 64 , 65 ). The observed neutropenia, historically called “benign ethnic neutropenia” and now more accurately “Duffy-associated neutrophil count” (DANC), does not eliminate effective inflammatory immune responses and is hypothesized to be asymptomatic in otherwise-healthy patients ( 66 68 ).…”
Section: Ackr1 Structure and Functionmentioning
confidence: 99%
“…The incidence of type 1 diabetes in children increased during the COVID-19 pandemic, [1][2][3][4] but studies have not discriminated between children with and without infection. We analyzed a large populationbased, individual-patient data set that included diagnoses of COVID-19 to determine whether there was a temporal association between COVID-19 and type 1 diabetes in children.…”
Section: Type 1 Diabetes Incidence and Risk In Children With A Diagno...mentioning
confidence: 99%
“…This phenotype is reported in 66.7% of individuals identifying as Black in the US and is associated with adequate total body neutrophils with a clinically insignificant lower peripheral neutrophil count . One study found that 23.8% of healthy people with the Duffy null phenotype have an absolute neutrophil count (ANC) below 2000/μL, the lower limit of normal of many reference ranges . With 70% of medical decisions based on laboratory values, reference ranges that do not reflect normal values for a significant proportion of the population may lead to iatrogenic harm.…”
mentioning
confidence: 99%
“…[11][12][13] As such, studies have proposed replacing BEN with more accurate terminology such as Duffy-null associated neutrophil count. 14 Established hematological reference ranges that are historically built on "normal" values among those of European descent disproportionately impact individuals who harbor the Duffy-null phenotype, most of whom are of Black race, leading to inaccurate clinical decision making and excessive diagnostic testing. [15][16][17] Gaining a comprehensive understanding of the demographics and clinical outcomes of patients with asymptomatic neutropenia, as well as variations in institutional references ranges, has the potential to change diagnostic and treatment paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Duffy antigens, as in the Fy(a‐b−) phenotype, prevents malaria merozoites from invading red blood cells (RBC), which explains why people living in geographic areas with high rates of malaria more commonly harbor this phenotype 11–13 . As such, studies have proposed replacing BEN with more accurate terminology such as Duffy‐null associated neutrophil count 14 …”
Section: Introductionmentioning
confidence: 99%